Enabling farmers to assess the soil quality implications of agricultural management options. Farmer citizen science in Madhya Pradesh, India - Rana, Jai Chand (2020)
This project has come out with an end to end solution for assessment of soil health and recommending management practices according to the soil health status. In this endeavor, DUS(Soil) a generic framework for identifying relevant soil health indicators was developed and this is a significant output of the project. It optimizes the methodology for developing management recommendations according to the soil health indicator status and the biophysical context. The SHIMAS tool which consists of a database of recommendations of cultural practices for different classes of the indicators, a GUI for the user to select the soil health indicators status of his field and a pop up window for the display of appropriate recommendations culled out from the database. Also, >450 farmers were trained on soil health assessment. Sustainability analysis of agriculture in the district in terms of stability of food grain production as well as that of area and productivity was also done.